Regime Shifts in Malaysian Exchange Rates - Tahir Ismail, Mohd; Isa, Zaidi (Malaysian Journal of Science, 2007)
There has been great interest in studying the non-linearity and regime shifts in financial time series. This is due to the realisation that the nonlinear feature in the data cannot be captured by a linear time series model. Therefore, a number of nonlinear model have been introduced to overcome this problem. In this paper, we adopt the 2-regime multivariate Markov switching vector autoregressive (MS-VAR) model with regime shifts in both the mean and the variance to extract common regime shifts behaviour of Malaysian currency exchange rates against four other countries namely the British pound sterling, the Australian dollar, the Singapore dollar and the Japanese yen between 1990 and 2005. It is found that the MS- VAR model with two regimes managed to detect common shifts in all the exchange rates series and this shows evidence of co-movement among all the exchange rates series. Furthermore, we found that all the exchange rates series are affected by the 1997 financial crisis. In addition, the MS-VAR model fitted the data better than the linear vector autoregressive model (VAR).